2012
DOI: 10.1103/physreva.85.024301
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of fermionic-field entanglement at infinite acceleration in relativistic quantum information

Abstract: We provide a simple argument showing that, in the limit of infinite acceleration, the entanglement in a fermionic field bipartite system must be independent of the choice of Unruh modes. This implies that most tensor product structures used previously to compute field entanglement in relativistic quantum information cannot give rise to physical results.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Here, we will apply the physical structure suggested by Ref. [22,23] that the ordering of the fermionic system should be rearranged by the sequence of particles and antiparticles in the separated region.…”
Section: Noninertial Framementioning
confidence: 99%
“…Here, we will apply the physical structure suggested by Ref. [22,23] that the ordering of the fermionic system should be rearranged by the sequence of particles and antiparticles in the separated region.…”
Section: Noninertial Framementioning
confidence: 99%
“…Because of the Unruh effect [6][7][8], entanglement between field modes degrades when at least one of the modes is observed by an accelerated observer [9][10][11][12][13][14][15][16][17][18][19][20][21]. Entanglement between two Dirac modes when one observer accelerates while the other moves uniformly was studied, indicating that the entanglement degrades with the acceleration.…”
Section: Introductionmentioning
confidence: 99%
“…Entanglement between two Dirac modes when one observer accelerates while the other moves uniformly was studied, indicating that the entanglement degrades with the acceleration. However, in contrast to the boson modes, whose entanglement approaches zero in the infinite acceleration limit [14][15][16][17][18][19][20][21], the Dirac modes have finite residual entanglement in this limit [9][10][11][12][13][14][15][16][17][18]. The case that two observers have the same acceleration was also studied, and by using the Bell states as the initial states, it was found that entanglement degradation depends on both the particle statistics and the initial state [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is known from fundamental studies that there are differences between the entanglement structure of the vacuum of fermionic and bosonic fields [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. However, a study of entanglement harvesting in fermionic setups has never been performed.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study of entanglement harvesting in fermionic setups has never been performed. A study of detector-based entanglement harvesting from a fermionic vacuum could resolve ambiguities in defining entanglement measures between disjoint regions of a fermionic field [32,[35][36][37][38][39][40][41]. The reasons why this has not been done can be traced back to fundamental difficulties associated with particle detector models for fermionic fields.…”
Section: Introductionmentioning
confidence: 99%